2022
DOI: 10.3390/nu14235129
|View full text |Cite
|
Sign up to set email alerts
|

ACE-Vitamin Index and Risk of Glaucoma: The SUN Project

Abstract: Background: Previous studies regarding antioxidant consumption and glaucoma have shown contradictory results. The aim of this study was to analyze the combined effect of the consumption of three vitamins (A, C and E) on the incidence of glaucoma in the SUN Project. Methods: For this study, 18,669 participants were included. The mean follow-up was 11.5 years. An index including vitamins A, C and E (ACE-Vitamin Index) was calculated. Vitamin intake was extracted from participants’ dietary data and vitamin supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Quercetin has shown a photopic negative response, an index of glaucomatous damage in murine models, proving it to be a viable anti-glaucoma supplement [ 361 ]. Quercetin has also been shown to reduce apoptotic cell death, thereby protecting retinal ganglion cells in rat models [ 362 , 363 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin has shown a photopic negative response, an index of glaucomatous damage in murine models, proving it to be a viable anti-glaucoma supplement [ 361 ]. Quercetin has also been shown to reduce apoptotic cell death, thereby protecting retinal ganglion cells in rat models [ 362 , 363 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Moreno et al found an inverse correlation between the multilocus genetic risk score (GRS) for POAG and plasma vitamin E concentration [ 57 ]. However, results from the SUN Project study suggested that the intake of vitamins A, C, and E alone may not confer a protective effect against glaucoma, but when taken together, they were associated with lower disease risk [ 58 ]. In our study, we observed a significant association between retinol and glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…9 , 10 Conversely, other cohort studies have not found that diet-derived antioxidants have a protective effect against glaucoma. 11 , 12 These apparently contradictory results may arise from the confounding factors and reverse causality in observational studies. Moreover, a randomized clinical trial (RCT) has failed to confirm the clinical benefit of a high intake of vegetables and fruits in POAG management.…”
Section: Introductionmentioning
confidence: 99%